Benthic macroinvertebrate diversity and function in an agricultural constructed wetland affected by agrochemical pressure (Seine-et-Marne, France) - Alexandre Michel; Jérémie D. Lebrun; Cédric Chaumont; Mathieu Girondin; Julien Tournebize; Virginie Archaimbault; Alienor Jeliazkov (Environmental Science and Pollution Research, 2025)

Contrasting Impacts of Cultivated Exotics on the Functional Diversity of Domestic Gardens in Three Regions with Different Aridity - Josep Padullés Cubino; Dorothy Borowy; Sonja Knapp; Zdeňka Lososová; Carlo Ricotta; Stefan Siebert; Jeannine Cavender-Bares; Daniel Sol; Alienor Jeliazkov; Christopher Swan (Ecosystems, 2021)
Cultivated exotic plants are often introduced for their aesthetic value and today comprise a substantial fraction of the flora of urban domestic gardens. Yet, their relative contribution to the functional diversity of domestic gardens and how it changes across different climate zones is insufficiently understood. Here, we investigated whether the effects of cultivated exotics on functional diversity of three plant traits related to plant aesthetics (that is, plant showiness, plant height, and leaf area) varied in suburban domestic gardens in three regions (Minnesota, USA; Alt Empordà, Spain; and central South Africa) that differ in aridity. For each garden, we calculated the mean and variance of each plant trait considering all co-occurring species and also splitting them into co-occurring cultivated exotics and natives. Our results revealed that mean plant showiness increased linearly with the proportion of cultivated exotics both across and within studied regions. Moreover, co-occurring cultivated exotics were, on average, showier than natives in all regions, but differences in their trait variances were context-dependent. The interaction between cultivated exotics and aridity explained variation in mean plant height and leaf area better than either predictor alone, with the effect of cultivated exotics being stronger in more arid regions. Accordingly, co-occurring cultivated exotics were taller and had larger leaves than natives in warmer and drier regions, while the opposite was true in cooler and wetter regions. Our study highlights the need to consider the combined effects of exotic species and climate in future studies of urban ecology.

Level-dependence of the relationships between amphibian biodiversity and environment in pond systems within an intensive agricultural landscape - Alienor Jeliazkov; François Chiron; Josette Garnier; Aurélien Besnard; Marie Silvestre; Frédéric Jiguet (Hydrobiologia, 2014)